Determinants of credit market in Indonesian banking industry - Siti Aisyah Tri Rahayu; Tri Mulyaningsih; Cahyadin, Malik (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study aims to find out determinants of conventional banks’ credit supply and demand in Indonesia between 2005 and 2014, a period after recovery from financial crisis in 1997/1998. Some literatures suggest that demand and supply of credit are determined by the rates of credit and bonds. This study is expected to contribute to the literature by considering the role of prudential policy, market structure and banks ownership on supply and demand for credits. By using the bank level yearly data, the Seemingly Unrelated Regression model is employed to manage simultaneity between demand and supply of credit. The empirical findings support the literature that in the case of Indonesian banking, demand and supply of credit are determined by the rates of lending and yields of bonds and the rates of Bank Indonesia Certificate (Sertifikat Bank Indonesia/SBI). This study also reveals that prudential regulation has even dampened the banks’ capability to supply lending. By implication, banks’ higher lending capacity could improve their supply of credits. Hence, larger banks are proved to be able to supply more credits than the smaller ones; whereas the demands for credit remain to be substantially determined by the macroeconomic conditions.